Laryngoceles with airway compromise complicating mucous membrane pemphigoid. (18th July 2018) - Wijaya, Carolyn; Morgan, Lucy; Novakovic, Daniel; Riminton, Sean
Abstract : Mucous membrane pemphigoid (MMP) encompasses a group of autoantibody-mediated, subepithelial blistering diseases, which primarily affect mucosal surfaces including oral, ocular, skin, genital, nasopharyngeal and oesophageal sites. We present a first description of laryngoceles as a manifestation of mucous membrane pemphigoid resulting in dynamic airway closure. Mucosal injury at other sites had previously resulted in pathergy and localised cicatrisation. We discuss successful combined medical and transcutaneous surgical intervention designed to avoid tracheostomy and minimise iatrogenic laryngeal cicatrisation.